Efficiency improvement of organizational-and-technological management of municipal heat-power systems - Басок, Борис Іванович; Євтухова, Тетяна Олександрівна (Eastern-European Journal of Enterprise Technologies, 2016)
A new method of efficiency improvement of MHP systems by optimizing the structure and parameters of multilevel organizational and technological management is proposed. The formalization of the method is implemented using the system of mapping of Cartesian products of the ordered sets of input variables and variables of control actions and feedbacks into output variables for each level of the management system. The problem of combination of organizational, technical and technological factors is solved using logical-mathematical functions, and interaction coordination of the MHP subsystems - by selecting the optimal degree of their organizational and functional independence within the limits determined by the above management tools. The possibilities of enhancing regional (city) programs of efficiency improvement of MHP systems by the interaction coordination of their participants taking into the account the size of investment sources received through the program and energy savings achieved are considered. According to scenarios of profit maximization, minimization of losses of fuel and energy resources and minimization of CO2 emissions, the problem of optimal control of the MHP system consisting of coal-fired boilers, gas-fired boilers, electric boilers, natural gas and biodiesel fuel cogeneration plants is solved. The simulation results, confirming the possibility of efficiency improvement of MHP systems by 20-40 % are presented.